PROGRAM PENGUATAN LITERASI KEUANGAN MELALUI PELATIHAN PENGELOLAAN KAS DAN ANGGARAN PADA SISWA SMK AL-KHAERIYAH PENGAMPELAN KOTA SERANG BANTEN - Faruq, Ahmad; Fitriah, Fitriah; Ruwaidatunnisa, Ratu; Cahya, Ardilla Amalia; Sonhaji, Sonhaji (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This Community Partnership Program (PKM) aims to improve the financial literacy of students at SMK Al-Khaeriyah Pengampelan, Serang City, Banten. The program addresses students’ low understanding of financial planning, cash recording, and simple budgeting, which affects their ability to manage income and expenses effectively. Activities were conducted through socialization, training, simulation, and mentoring. The training covered basic financial literacy concepts, cash management techniques, budgeting procedures, and simple record-keeping using cash books and digital tools. Evaluation was carried out through pre-tests and post-tests to measure learning improvement, supported by observations of students’ practical performance in managing organizational finances. The results showed a significant increase in students’ financial knowledge and skills, especially in managing cash and preparing basic budgets. This program is expected to build students’ independence in financial management and strengthen their readiness to face future challenges in the workplace or entrepreneurship.